Electronic Portfolio as a Mean of Reflection Formation for Students Learning - Margolis A.A; Safronova M.A; Drobyazko A.A; Kuravsky L.S; Golovanova I.A; Pominov D.A (Moscow State University of Psychology and Education, 2021)
The article presents the results of a study aimed at the reflection formation of students to the educational program they are mastering as a program of preparation for professional activity through a specially organized educational environment, including the use of the "Electronic Portfolio" tool and regular interaction with a supervisor. The study involved students of bachelor's programs of the faculty of "Psychology of Education" MSUPE - "Psychology and pedagogy of primary education (primary school teacher)" (N=21 people) - experimental group and "Psychology and pedagogy of education (psychologist)" (N=22 people) - control group. A questionnaire was used to study the reflection formation towards mastering the main professional educational program. The results obtained make it possible to say that the specially-organized work of the supervisor of the mini-group, mediated by the use of an electronic portfolio that records the development of the student's professional competencies, can provide conditions for the formation of a student's reflection to learning. An electronic portfolio can be used as a navigator in the educational program and a means of organizing reflection of students' professional competencies in professional activity.